The judiciary in Malaysia: its role and challenges / Azian Othman - Azian, Othman (Faculty of Law, 1987)
Thi s project paper concerned wi th the role of the Judi ci ary and its challenges. The Judiciary occupies the highest position in our system of administration of justice. They play an effective role in protecting and defending the Constitution and dispensing justice in accordance with law. The Judi ci ary today has the power to interpret the Constitution and lay down what the Constitution means. It is the guardian of the Constitution which is the supreme law of the land. By the nature of thei r oath judges are to preserve, protect and defend the Consti tuti on.